1982
DOI: 10.1111/j.1365-2621.1982.tb12731.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prerigor Pressurization on the Emulsifying Capacity of Muscle Protein

Abstract: The emulsifying capacities of pressure treated and control muscle homogenates, sarcoplasmic protein and myofibrillar proteins of ovine and bovine longissimus muscles were determined at 2, 6, 24 and 168 hr postmortem. The pH of the intact muscle, muscle homogenate and myofibrillar protein extract were taken at these times. Before onset of rigor mortis, the emulsifying capacity of muscle homogenate from the control samplcs was higher than the pressure treated samples. At 24 and 168 hr postmortem, the pressure tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Such findings suggest that lysosomal enzymes leaked out of lysosomes by hydrostatic pressure at 202.7 MPa or higher. Elgasim et al 16 ) reported that fJ-glucuronidase migrated from sedimentable to unsedimentable fractions when bovine longissimus muscle was pressurized at 103.5 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings suggest that lysosomal enzymes leaked out of lysosomes by hydrostatic pressure at 202.7 MPa or higher. Elgasim et al 16 ) reported that fJ-glucuronidase migrated from sedimentable to unsedimentable fractions when bovine longissimus muscle was pressurized at 103.5 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation of micro tubules , cilium basal body, and microfilaments/,7) disappearance of ribosomes and Golgi complexes,2) disruption of sarcoplasmic reticulum,8) and swelling of mitochondria 9 ) have been observed. No study, however, has been done to examine the effects of high pressure on lysosomes, which contain a large amount of hydrolytic enzymes including cathepsins and acid phosphatase and are important in intracellular metabolism.…”
mentioning
confidence: 99%
“…The effect of prerigor pressure treatment on the EC of meat proteins in sausage batters was reported [84]. Before the onset of rigor mortis, the EC of muscle homogenate from the control samples was higher than the pressure treated samples.…”
Section: The Effect Ofpostmortem Changesmentioning
confidence: 99%
“…The results of a number of studies indicate that pressure can be used to alter the properties of muscle proteins (Cheftel and Culioli 1997; Colmenero 2002) including increased solubility, aggregation and gelation (MacFarlane 1974; MacFarlane and McKenzie 1976; Elgasim et al. 1982; MacFarlane et al.…”
Section: Introductionmentioning
confidence: 99%